OPTIMASI PROSES SAND CASTING DALAM UPAYA REDUKSI CACAT PENGECORAN LOGAM BERDASARKAN PENGARUH POURING TIME, SUHU TAPPING, DAN SUHU POURING PADA PT. X - Ahmad Roihan Al Muttaqi (Universitas Muhammadiyah Metro, 2026)
The sand casting process is widely used due to its flexibility in producing components with various geometries. However, casting defects remain a major issue as they reduce product quality and increase production losses. This study analyzes the effect of pouring time, tapping temperature, and pouring temperature on defect tendencies in deckdrain products produced by sand casting at PT X. A descriptive quantitative method was applied using production observation data collected during internship activities on January 12–15, 2026. The analysis included visual defect identification, defect classification, pouring time measurement, and temperature evaluation from tapping to pouring. The results showed six dominant defects: misrun, blow hole, cold shut, metal penetration, rat tail, and inclusion. The average pouring time was highest in the body part at 19.39 s, followed by grating at 11.22 s and filter at 7.14 s. Tapping temperature ranged from 1592–1673 °C, while pouring temperature ranged from 1510–1605 °C, with an average temperature drop of 52.75 °C. These results indicate that variations in pouring time and heat loss can reduce metal fluidity and increase the risk of misrun and cold shut defects. Therefore, defect reduction should focus on controlling pouring time and temperature for each